'Let's check-in with our tummies': Orienting to feelings-talk in group supervision for psychotherapy counsellors. (October 2018) - Hutchby, Ian; Dart, Alison
This article examines a particular kind of business-opening activity found in a specific, and little analysed, type of institutional group meeting: group supervision for psychotherapeutic counsellors. The data consist of a particular set of activities that occur in the initial stages of these meetings, which are neither the kind of pre-meeting talk identified by previous research on interaction in meetings, nor specifically the business of group supervision itself. This phase, referred to as the 'check-in', functions as an interim stage between small talk and getting down to business. The analysis shows how the check-in comprises a highly structured set of linguistic sequences whose production is bound up with one of the key interactional features of group supervision: the collaborative orientation to the production and relevance of 'feelings-talk'.